2020
DOI: 10.1097/ccm.0000000000004428
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Clinical Impact of Rapid Response Electroencephalography: The DECIDE Multicenter Prospective Observational Clinical Study*

Abstract: Objectives: To measure the diagnostic accuracy, timeliness, and ease of use of Ceribell rapid response electroencephalography. We assessed physicians’ diagnostic assessments and treatment plans before and after rapid response electroencephalography assessment. Primary outcomes were changes in physicians’ diagnostic and therapeutic decision making and their confidence in these decisions based on the use of the rapid response electroencephalography system. Secondary outcomes were time to electroencep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 51 publications
1
76
0
Order By: Relevance
“…However, in the present study patients were included if an EEG was performed within 24 h of symptom onset. Thus, probably capturing a more realistic picture of regular delayed conventional EEG performance in many ERs [5]. In addition, longer, continuous EEG recordings in the ER could improve the characterization of patients along the ictal-interictal continuum and its neuroimaging correlate obtained on pCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study patients were included if an EEG was performed within 24 h of symptom onset. Thus, probably capturing a more realistic picture of regular delayed conventional EEG performance in many ERs [5]. In addition, longer, continuous EEG recordings in the ER could improve the characterization of patients along the ictal-interictal continuum and its neuroimaging correlate obtained on pCT.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke and post-ictal epileptic phenomena often mimic SE without prominent motor symptoms (nonconvulsive SE [NCSE]) [4]. In such cases, an electroencephalogram (EEG) is necessary to confirm diagnosis, but even at tertiary hospitals that deal with neurological emergencies, access to EEG can be delayed by 4 h or longer [5]. Seizure duration is one of the main modifiable prognostic factors in SE and reductions in this time are closely correlated with better outcomes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This study also noted that physicians reported using the Rapid‐EEG contributed to changing clinical management and expedited discharge. Vespa et al 38 in a multicenter clinical study Does Use of Rapid Response EEG Impact Clinical Decision Making (DECIDE) trial assessed the impact on physicians’ diagnostic accuracy before and after using the Ceribell system. They found that relying on rapid response EEG information at the bedside improved the sensitivity and specificity of physicians' seizure diagnosis.…”
Section: Results: 20 Years Of Progress In the Application Of New Noni...mentioning
confidence: 99%
“…They can rely on their own bedside visual EEG review combined with the Rapid-EEG’s Brain Stethoscope function [ 43 ]. In three clinical studies so far, staff with minimal or no EEG experience increased their accuracy of seizure diagnosis significantly by relying on either Brain Stethoscope alone [ 15 , 16 ] or combined with bedside visual EEG review [ 17 ]. It is important to note that a much larger number of EEG cases often do not result in seizure output, and hence, use of the algorithm will lead to prevention of overtreatment of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…When actionable EEG interpretations are not immediately available, treatment decisions are made on the basis of clinical suspicion alone, which results in the potential for missing or undertreating some patients with nonconvulsive seizures and overtreating a significantly larger number of patients without seizure activity who may not need aggressive antiseizure medications [ 13 , 14 ]. To provide timely access to EEG, novel rapid EEG systems can be used to enable physicians and allied health professionals to acquire EEG within minutes and stream the data in real time to the cloud, where a machine learning-derived classification algorithm can be applied [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%